Subalternity and society: Servants, careerists and marginalized in "A world for Julius" by Alfredo Bryce Echenique - Valenzuela Garcés, Jorge (2012)
An approach to the universe of servants in A world for Julius by Alfredo Bryce Echenique shows that the dynamics of domination depicted in the novel can be better understood if we can prove that the universe from which these references causing exclusion and differentiation from the other are generated, is the universe of the own Dominator, who thus can only build that one who is different from himself with elements that are essential and that is why he is so configured. In this way the subaltern subject is known and visualized (stereotyped), and is marked through strategies such as stigmatization. In this article we try to identify how these two discursive procedures occur, and how their role in the novel has as a purpose to configure a universe marked by the degradation and the underestimation of the other.